Using Metacognitive Strategy of Across Gender and English Proficiency in Junior High School (RETAIN, 2020)
This article contains study about strategies that students use when they read English text. The purpose of this study is (1) to know the differences student’s metacognitive reading strategy in low, middle, and high level of English proficiency (2) to know the differences metacognitive awareness of Male and Female in reading comprehension. The subject of this study is second grade junior high school student. The sample is 25 Male students and 25 Female students in different class and teacher. This study presents ex post facto study to compare level of English proficiency and across gender with Metacognitive Awareness. The data collected by using Formative score in class and Metacognitive Awareness of Reading Strategy Inventory (MARSI) test. The researcher also interviews the students to complete the data. This study use one way ANOVA analysis to analyze different English Proficiency and Independent sample t-test analysis to compare data of across gender in metacognitive awareness of reading strategy.